Fast view synthesis optimization algorithm based on texture smoothness - Huan DOU; Ke-bin JIA; Rui-lin CHEN; Yun-zhi XIAO; Qiang WU (Tongxin xuebao)
A fast algorithm was proposed in order to reduce the v ew synthesis optimization (VSO) process in depth cod-ing for 3D-HEVC based on texture map smoothness.With the coding nformation derived from texture video sequences,the pixel regularity of smooth texture region was analyzed to set the skip rule using the properties of intra DC prediction and statistical methods.Then the depth regions corres to the flat texture map regions could be extracted and the VSO process of pixels belonging to this type of depth could be skipped.Experimental results show the effective-ness of the proposed algorithm.